2018
DOI: 10.1007/s10803-018-3737-0
|View full text |Cite
|
Sign up to set email alerts
|

Social Stories for Children with Autism Spectrum Disorder: Validating the Content of a Virtual Reality Program

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that affects socio-emotional skills and perspective-taking abilities. Although social stories in a form of virtual reality program can help children with ASD, developing them and identifying appropriate responses might be subjective and thus challenging. Using Delphi method, and guided by general case training, we involved 63 parents and clinicians of individuals with ASD, in two rounds of online iteration to refine the stories. Scenarios that rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Whilst numbers in the present study were too small to analyse this formally, a visual analysis suggested that, if anything, increasing appropriate behaviours was more effective than reducing inappropriate behaviours. Whilst speculative, it may be that the engaging and appealing features of visual media and a touch screen digital device increases the motivation and interest of children on the autism spectrum leading to promising gains in self-directed learning, independence, and pro-social outcomes (Ghanouni et al 2019;Hong et al 2017;Kim et al 2014;Vandermeer et al 2015). As an example, the SOFAapp enables photos taken by the digital device (tablet or smartphone) to illustrate the stories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst numbers in the present study were too small to analyse this formally, a visual analysis suggested that, if anything, increasing appropriate behaviours was more effective than reducing inappropriate behaviours. Whilst speculative, it may be that the engaging and appealing features of visual media and a touch screen digital device increases the motivation and interest of children on the autism spectrum leading to promising gains in self-directed learning, independence, and pro-social outcomes (Ghanouni et al 2019;Hong et al 2017;Kim et al 2014;Vandermeer et al 2015). As an example, the SOFAapp enables photos taken by the digital device (tablet or smartphone) to illustrate the stories.…”
Section: Discussionmentioning
confidence: 99%
“…One way to overcome research inconsistencies is to use digital technology within RCTs (Goldsmith and LeBlanc 2004), and social stories for children on the autism spectrum may be particularly amenable to delivery through digital technology (e.g. Kennedy et al 2019;Ghanouni et al 2019). Digital storytelling is a combination of traditional oral storytelling supported by personalised digital images (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…SS for children on the autism spectrum may be particularly amenable to delivery through digital technology (e.g. Kennedy et al 2019;Ghanouni et al 2019) as there are benefits of digitally-mediated SS for those who have difficulties with social interaction, enabling greater intensity of interaction with the content of the story. Digital technology can provide a more consistent and structured environment for the story, enabling repetition and direct feedback, and can offer the child more control over the learning experience.…”
Section: Introductionmentioning
confidence: 99%
“…Another important area is the use of VR to improve emotional skills. For example, Ghanouni et al. (2019) developed a validated library of VR social stories focused on perspective-taking that offer gradual levels of emotion intensity and difficulty.…”
Section: Clinical Applications and Recommendations ∗mentioning
confidence: 99%